The welfare costs of tiebout sorting with true public goods - Beat Hintermann; Florian Kuhlmey (University of Basel, Center of Business and Economics (WWZ), 2018)
We develop a model of Tiebout sorting based on decentralized income taxation, which allows for spillovers and imperfect rivalry in consumption of the publicly provided good. We identify three sources of welfare loss from decentralization: Imperfect redistribution, inter-jurisdictional free-riding, and inecient residential choice. Whereas the welfare loss from imperfect redistribution decreases and that from free-riding rises unambiguously as the publicly provided good becomes more pure, the welfare loss from the inecient residential choice depends non-monotonically on spillovers and rivalry. The equilibrium can be characterized by relative crowding of either the rich or the poor municipality. Our results imply that the characteristics of the publicly provided good are an important determinant for the welfare costs of decentralization.
Keywords: H21; H23; H41; H77; R13; R23; R50; Q58; 330; Public goods; Tiebout; local income taxation; scal federalism; decentralization; free-riding